Wybrane problemy życia codziennego Polaków na podstawie listów opublikowanych na łamach „Przyjaciółki” w latach 1956–1970 - Słowiński, Konrad (Pamięć i Sprawiedliwość, 2013)
The article presents selected problems of everyday life of Poles in the years 1956–1970 of the Gomułka era on the basis of letters sent to the weekly magazine „Przyjaciółka”. The main idea lying behind the article was the desire to present the everyday life of average Poles. The obvious conclusions are that citizens of the People’s Republic of Poland at that time did not have an easy life. The reality of everyday life presented in the letters sent to „Przyjaciółka” was fundamentally different from the official propaganda version presented by the Gomułka team. When Gomułka was elected the First Secretary of the Communist Party in 1956, Poles were hoping for changes in the country. However, everyday life of average citizens remained the same. The reality under Communism was still sad and gray. This was reflected in the letters sent to „Przyjaciółka”, where people constantly complained about the lack of flats or terrible living conditions, the ailing healthcare, empty shops and defective goods. Generally, in the eyes of average citizens, inhabitants, patients and consumers of that time, the Gomułka era was not much different from the times of Bolesław Bierut. Everyday life in Communist Poland of the Gomułka era, in the time of the small stabilization, was still full of an- xiety and torment. However, we need to remember that despite the hopelessness of certain situations and the growing number of problems which Poles had to face every day, it was still possible “to get through” in Communist Poland. For us, the times of Communist Poland may even present a certain amount of charm. When looking back at the past from our perspective, many people smile remembering Polish cars, in which, despite their small capacity, people managed to cram tons of different objects, „Frania” – the Polish washing machine or crimplene trousers. And the letters sent to „Przyjaciółka” are just a small, sometimes humorous or even incredible, part of the difficult reality of that time.